Propriedade intelectual e renda no capital-informação - Ormay, Larissa Santiago (2018)
Starting from the premise that the spoliation movement characteristic of the primitive accumulation of capital has not been exhausted at all, but is broadly and systematically reissued in order to privatize social relations, the thesis is based on the correlation between the enclosure of lands and the "enclosure" of knowledge. This research demonstrates the analogy between the rent of land described by Karl Marx, originated by the "traditional" private property, and the informational rent, derived from the intellectual property that expands globally in the Capital-Information, a post-Fordist context that highlights the informational work. This theoretical development is applied to a case study which investigates the conflict between the free access and the private appropriation of scientific and technological knowledge involved in the creation of quantum technologies. It is observed that the knowledge circulation in a Physics area called Quantum Information is impaired by the incidence of intellectual property rights, despite the existence of open access tools, such as the arXiv digital platform. At the end, some considerations are made about the impacts of Capital-Information on the contemporary democratic project.